Transition Management for Improving the Sustainability of WASH Services in Informal Settlements in Sub-Saharan Africa—An Exploration - Silvestri, Giorgia; Julia, M. Wittmayer; Karlijn, Schipper; Kulabako, Robinah; Oduro-Kwarteng, Sampson; Nyenje, Philip; Komakech, Hans; Roel, van Raak (Sustainability, 2018)
This paper explores how transition management processes can be designed to address the unsustainability of water, sanitation, and hygiene (WASH) services in informal settlements in cities in Sub-Saharan Africa. The unsustainability of services related to WASH in informal settlements in Sub-Saharan Africa is deeply embedded in current societal and governance structures, cultures, and practices; it is context-dependent and involves numerous actors with different interests. Based on a literature review and empirical work in Arusha (Tanzania), Dodowa (Ghana), and Kampala (Uganda), we identify five context dimensions that account for the unsustainability of WASH services: (a) multiplicity of WASH practices, structures, and arrangements; (b) governance capacities for WASH services and maintenance; (c) landownership for sustainable access to WASH; (d) public participation in decision-making related to WASH; and (e) socio-economic inequalities governing access to WASH. These dimensions pose numerous conceptual and application challenges for transition management. Based on these challenges, recommendations are formulated for the design of a contextualized, participatory transition management process that is not only functional, but also emancipatory.